Response of Sorghum Varieties to Organic and Inorganic Fertilizer Strategies in Sudan Savanna of Nigeria: Productivity, Nitrogen, and Water Use Efficiencies - Ajeigbe, Hakeem A.; Akinseye, Folorunso M.; Tukur, Abdulazeez; Inuwa, Abubakar Hassan; Whitbread, Anthony M. (2024)
Experiments were conducted to evaluate the response of different sorghum varieties to micro-dosing fertilization strategies on yield and yield traits, as well as the impact on nitrogen fertilizer and water use efficiency (NUE and WUE). In addition, the benefit-cost ratio of sorghum cultivation under different fertilization strategies in the Sudan savanna zone of Nigeria was analyzed. The experiment included eight fertilizer micro-application strategies as well as two control and three sorghum varieties. Our results showed that most agronomic indicators differed significantly between years, varieties, and fertilization strategies. However, the application of 100g hill-1 poultry manure plus 3g NPK hill-1 resulted in the highest average grain yield > 2000 kg ha-1 at both study sites (BUK and Minjibir). This means that the grain yield is 86% and 132% higher than the average grain yield with zero fertilization. There were extremely significant differences between NUE and WUE fertilization strategies and varieties at the two sites. At BUK and Minjibir, NPK applied with 3 g of hill-1 had the highest NUE with an average of 37.6 and 40 kg grain/kg N. Application of 100 g of poultry manure plus 3g of NPK hill-1 resulted in the highest average WUE of 6.1 and 5.6 kg grain/mm for BUK and Minjibir, respectively. BUK (3.2) and Minjibir (3.6) had the highest net income and benefit-to-cost ratios when applying 3 grams of NPK per hill. The adoption of micro-dosing fertilization strategies by smallholder farmers provides a good opportunity to prevent long-term soil fertility limitations and thereby increase sorghum productivity and farmer incomes by recommending multiple-choice fertilization strategies for improved sorghum varieties.